Influence of voltage deviation on the angular speed of series-excitated DC motors - Sinyavsky, O.; Savchenko, V. (Energy and Automation, 2025)
Series-excited DC motors are the most common DC motors used in mobile machines.In these motors, the magnetic flux depends on the motor load. Since the magnetization curve of the electric motor is nonlinear, it is not possible to obtain an analytical expression for the mechanical characteristics of the motor. Therefore, the operation of the motor is considered in an unsaturated magnetic system and a saturated one.The purpose of the study is to analyze the influence of voltage deviation on the angular speed of working machines with a series-excited DC motor.As a result of the conducted research, the dependences of the angular speed of a series-excited DC motor on voltage for working machines with different types of mechanical characteristics in an unsaturated and saturated magnetic system were established.It was established that the law of change of the angular speed of the electric drive when the supply voltage deviates is determined by the mechanical characteristic of the working machine. For working machines in which the moment of static resistance does not depend or linearly depends on the angular speed, the angular speed changes linearly with the change in voltage. For working machines with nonlinear mechanical characteristics, the change in the angular speed of the electric drive when the voltage deviates occurs according to a complex algorithm.The influence of the thyristor voltage converter on the power supply network was also studied. The third, fifth and seventh harmonics were found in the harmonic spectrum.Key words: electric drive, series-excited DC motor, angular speed, voltage deviation, mechanical characteristic of the working machine, thyristor voltage converter, higher harmonics